Ghana: Poverty reduction over thirty years - Andy McKay; Jukka Pirttilä; Finn Tarp (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2015)
Ghana is relatively rare among Sub-Saharan African countries in having had sustained positive growth every year since the mid-1980s. This paper analyses the nature of the growth and then presents an analysis of the evolution of both consumption poverty and non-monetary poverty outcomes over this period, showing improvements in almost all indicators over this period. At the same time, inequality has risen over the past 20 years and spatial inequality, in both monetary and non-monetary outcomes, remains an important concern. This increase in inequality is one reason why growth has not led to faster poverty reduction.
Keywords: I32; O10; O40; O55; 330; Ghana; growth; poverty; non-monetary poverty; inequality